High spatial resolution spiral first‐pass myocardial perfusion imaging with whole‐heart coverage at 3 T. Issue 2 (11th March 2021) - Wang, Junyu; Yang, Yang; Weller, Daniel S.; Zhou, Ruixi; Van Houten, Matthew; Sun, Changyu; Epstein, Frederick H.; Meyer, Craig H.; Kramer, Christopher M.; Salerno, Michael
Abstract : Purpose: To develop and evaluate a high spatial resolution (1.25 × 1.25 mm 2 ) spiral first‐pass myocardial perfusion imaging technique with whole‐heart coverage at 3T, to better assess transmural differences in perfusion between the endocardium and epicardium, to quantify the myocardial ischemic burden, and to improve the detection of obstructive coronary artery disease. Methods: Whole‐heart high‐resolution spiral perfusion pulse sequences and corresponding motion‐compensated reconstruction techniques for both interleaved single‐slice (SS) and simultaneous multi‐slice (SMS) acquisition with or without outer‐volume suppression (OVS) were developed. The proposed techniques were evaluated in 34 healthy volunteers and 8 patients (55 data sets). SS and SMS images were reconstructed using motion‐compensated L1‐SPIRiT and SMS‐Slice‐L1‐SPIRiT, respectively. Images were blindly graded by 2 experienced cardiologists on a 5‐point scale (5, excellent; 1, poor). Results: High‐quality perfusion imaging was achieved for both SS and SMS acquisitions with or without OVS. The SS technique without OVS had the highest scores (4.5 [4, 5]), which were greater than scores for SS with OVS (3.5 [3.25, 3.75], P < .05), MB = 2 without OVS (3.75 [3.25, 4], P < .05), and MB = 2 with OVS (3.75 [2.75, 4], P < .05), but significantly higher than those for MB = 3 without OVS (4 [4, 4], P = .95). SMS image quality was improved using SMS‐Slice‐L1‐SPIRiT as compared to SMS‐L1‐SPIRiT ( P < .05 for both reviewers). Conclusion: We demonstrated the successful implementation of whole‐heart spiral perfusion imaging with high resolution at 3T. Good image quality was achieved, and the SS without OVS showed the best image quality. Evaluation in patients with expected ischemic heart disease is warranted. Abstract : Click here for author‐reader discussions